2013
DOI: 10.30935/cedtech/6102
|View full text |Cite
|
Sign up to set email alerts
|

Principals' Perceptions of the Importance of Technology in Schools

Abstract: A sample of 311 principals from a large metropolitan area in the southwest region of the U. S. responded to a questionnaire that addressed public school principals' perceptions related to the major functions of technology in their schools. Principals reported that the major functions of technology were: (a) communication, (b) instruction, (c) data sharing and management, (d) a resource, (e) administrative tasks, and (f) student learning. Male principals felt that technology was used as a resource and for admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…A study by Alkrdem (2014) showed that the technological leadership behavior of “headteachers” did not differ with respect to their gender in Saudi Arabia; however, according to Banoglu (2011), female technology leaders were more effective compared with male technology leaders in Turkey. In addition to these findings, Waxman et al (2013) stated that gender influences how leaders perceive the functions of technology in their schools in the United States. In Malaysia, previous research has shown that the gender of school leaders did not have significant influence on technology leadership (Hamzah et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 96%
“…A study by Alkrdem (2014) showed that the technological leadership behavior of “headteachers” did not differ with respect to their gender in Saudi Arabia; however, according to Banoglu (2011), female technology leaders were more effective compared with male technology leaders in Turkey. In addition to these findings, Waxman et al (2013) stated that gender influences how leaders perceive the functions of technology in their schools in the United States. In Malaysia, previous research has shown that the gender of school leaders did not have significant influence on technology leadership (Hamzah et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Before the pandemic, the principals' roles and leaderships are often researched to ensure and improve the integration of ICT into classrooms. It was often found that positive attitude of the principals towards ICT would positively impact the support given to the teachers in using the ICT (Mulwa & Kyalo, 2013;Neyland, 2011;Polizzi, 2011), the effectiveness of the implementation (Fessehatsion, 2017;Waxman et al, 2013) and the teachers' belief (Alghamdi & Prestridge, 2015). For example, a study conducted by Serhan (2007) on 200 principals in Arab countries suggests that principals have a willingness to apply technology.…”
Section: Principals' Roles In Th E Implementation Of Online Learningmentioning
confidence: 99%
“…Instructional leaders will cultivate structure alignment and cohesive groups by training, modeling, and structuring however digital tools are used, together with an LMS. The results from this study and therefore the existing literature [84,85] counsel that directors will remodel the attitudes of lecturers after they model the utilization of technology and an LMS. A study conducted by Sun et al [86] found a correlation between teachers' attitudes toward technology and learners' satisfaction of instruction.…”
Section: Discussionmentioning
confidence: 66%